1997
DOI: 10.1212/wnl.48.5.1290
|View full text |Cite
|
Sign up to set email alerts
|

Oral phenylalanine loading in dopa‐responsive dystonia

Abstract: To determine if there is abnormal phenylalanine and biopterin metabolism in patients with dopa-responsive dystonia (DRD), we measured plasma levels of phenylalanine, tyrosine, biopterin, and neopterin at baseline, and 1, 2, 4, and 6 hours after an oral phenylalanine load (100 mg/kg). Seven adults with DRD, two severely affected children with DRD, and nine adult controls were studied. All patients had phenylalanine and tyrosine concentrations within the normal range at baseline. In the adult patients, phenylala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 1 publication
0
38
0
Order By: Relevance
“…Although individuals with DRD never develop hyperphenylalaninemia, a subclinical defect in phenylalanine metabolism caused by partial BH4 defi ciency in the liver can often be detected by the phenylalanine loading test, which analyzes plasma phenylalanineto-tyrosine ratios following an oral phenylalanine load 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although individuals with DRD never develop hyperphenylalaninemia, a subclinical defect in phenylalanine metabolism caused by partial BH4 defi ciency in the liver can often be detected by the phenylalanine loading test, which analyzes plasma phenylalanineto-tyrosine ratios following an oral phenylalanine load 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis can be based on clinical fi ndings (including dramatic and sustained response to low doses of L-dopa), plasma levels of phenylalanine/tyrosine after an oral phenylalanine load and molecular analysis of GCH1 gene [1][2][3][4][5][6] .…”
mentioning
confidence: 99%
“…Based on this, a Phe loading procedure has been proposed (Hyland et al 1997) and different values of Phe/Tyr 4 hours after the loading have been suggested as a critical threshold for the diagnosis: 4.5 (Saunders-Pullman et al 2000), 7.5 (Bandmann et al 2003), 5.25 (Saunders-Pullman et al 2004. In spite of high sensitivity and specificity of the test, false negatives (Saunders-Pullman et al 2004) and positives (Bandmann et al 2003) were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Neopterin and biopterin were determined in the first morning urine sample and CSF according to the method published elsewhere (Antonozzi et al 1988). Phe and Tyr were measured by ESI-MS/MS (Chace et al 1993) in dried blood spots at baseline and 1, 2, 3, 4, 5 and 6 h after oral Phe loading (100 mg/kg body weight) (Hyland et al 1997) .…”
Section: Methodsmentioning
confidence: 99%
“…A low-protein breakfast was allowed before and no further food was permitted during the test. Phe, tyrosine (Tyr) and Phe/Tyr ratio from capillary blood samples were measured at baseline, and 1, 2, 3, 4, 5, 6 h after Phe loading, as previously described [20]. Phe and Tyr were measured using standard sensitive quantification method based on a liquid chromatographyelectrospray ionization-tandem mass spectrometry [21].…”
Section: Methodsmentioning
confidence: 99%